Acknowledging, measuring and acting on the importance of water for food and nutrition - Young, S. L.; Bethancourt, H. J.; Cafiero, C.; Gaitán-Rossi, P.; Koo-Oshima, S.; McDonnell, Rachael; Melgar-Quiñonez, H.; Neufeld, L. M.; Oenema, Stineke; Pérez-Escamilla, R.; Viviani, S.; Frongillo, E. A. (Springer, 2023)
Recognizing the importance of experiences with water insecurity in the context of food and nutrition is a powerful way to act on the Food and Agriculture Organization’s call to “take water action for food and be the change” on World Food Day.